Bioremediation in Aquatic Systems: A Literature Review on Fish as Natural Agents for Water Quality Management in Aquaculture - Sujadi, Frentina Murti; Anjaini, Jefri; Kusuma, Baruna; Nurhabib, Asro; Setiyaningsih, Lilik; Kurniawan, Setyo Budi (Aquaculture Department, University of Mataram, 2025)
Aquatic animals play a significant role in bioremediation processes in aquatic environments through their natural activities, such as filtering particles, aerating water, and nutrient cycling. This study aims to review the use of aquatic animals as natural biofilters in aquaculture systems, highlighting their efficiency and the supporting role of microbial technology. The method used is a literature review from 24 relevant articles published between 2015 and 2024. Results show that species such as goldfish, catfish, and eels can reduce organic waste, regulate plankton composition, and enhance oxygen levels. Moreover, the integration of probiotics and biotechnologies such as microbial fuel cells, bioaugmentation, and biostimulation improves pollutant degradation and water quality. The implications of these findings suggest that aquatic animal-based bioremediation is a promising and environmentally friendly approach to sustainable aquaculture, reducing reliance on antibiotics and chemical disinfectants while supporting ecological balance and animal health.